2007
DOI: 10.1111/j.1939-165x.2007.tb00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver aspirate from a Shar Pei dog

Abstract: A 5-year-old, neutered male, Shar Pei dog was presented with weight loss, anorexia, lethargy, stranguria, and distal limb edema. Clinicopathologic abnormalities included anemia, an inflammatory leukogram, azotemia, icterus, urinary tract infection, and hepatomegaly with a markedly hypoechoic liver. Cytologic findings in a fine-needle aspirate of the liver included large amounts of amorphous, pink, extracellular matrix between hepatocytes. The amorphous material was congophilic using Congo red stain on a hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…In the present case, we detected amyloid in cytologic smears stained with Wright–Giemsa and DFS stain. The cytologic appearance of amyloid with Wright–Giemsa staining was similar to that found in previous cases and appeared as amorphous pink‐ to purple‐colored material between hepatocytes . The DFS stain has not previously been reported in cytologic smears from cats and was used in this case as in human samples it has been a more sensitive method for amyloid detection compared to the Congo red stain .…”
Section: Discussionsupporting
confidence: 81%
“…In the present case, we detected amyloid in cytologic smears stained with Wright–Giemsa and DFS stain. The cytologic appearance of amyloid with Wright–Giemsa staining was similar to that found in previous cases and appeared as amorphous pink‐ to purple‐colored material between hepatocytes . The DFS stain has not previously been reported in cytologic smears from cats and was used in this case as in human samples it has been a more sensitive method for amyloid detection compared to the Congo red stain .…”
Section: Discussionsupporting
confidence: 81%
“…The liver gross examination revealed a swollen, puffy appearance, and there are several cracks and fractures on the surface which have resulted in fatal hemorrhage [9]. (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Familial amyloidosis has been described in certain dog breeds. The most commonly affected breeds are Beagles, Shar-Peis, and Foxhounds [9].…”
Section: Senilementioning
confidence: 99%
“…The most common site for amyloid deposition in dogs is the kidney, resulting in progressively reduced kidney function and therefore clinical and biochemical changes compatible with chronic kidney disease (Slauson et al 1970). Diagnosis of amyloidosis can be challenging, as it is not reliably diagnosed with fine needle aspirate cytology alone and requires Congo red staining; diagnosis typically requires histology however a cytological diagnosis of hepatic amyloidosis has been reported in one Shar Pei (Flatland et al 2007). When compared with non-Shar Pei dogs, it has been shown that Shar Pei develop renal amyloidosis at a significantly younger age (Segev et al 2012).…”
Section: Discussionmentioning
confidence: 99%